The Mediating Role of Intention to Adopt in the Relationship between the Information Processing Requirements and Information Processing Capacity: The Application of Cloud Computing in Thai Auto Supply Chain - Khomsan Laosillapacharoen; Sudawan Somjai; Akarapitta Meechaiwong; Tanapon Vipaporn (International Journal of Supply Chain Management, 2019)
The main purpose of this study is to examine the relationship between information processing requirements and information processing capacity. Additionally, the intention to adopt is examined the mediating role of intention to adopt in the relationship between information processing requirements and information processing capacity in the Thai automobile industry is examined. The study has broached the conceptual model as an application of cloud computing in the Thai automobile supply chain. The SEM-PLS is adopted to examine the model. The Thai automobile industry is taken as the sample of the study. The study is of the view that the industry of cloud computing is growing rapidly to support the supply chain activities. However, there is lack of academic research on analyzing the application of cloud computing in managing supply chain theoretically. It has been revealed through literature review that the focus of researches is on identifying the applications and architectures of cloud environment. Moreover, the study proposes different limitations and opportunities related to cloud computing. The adoption of cloud computing by an organization has been examined theoretically in this research through use of information processing view and classical diffusion theory. Practitioners and academicians are given an understanding of the circumstances, which influence the firm to adopt cloud-computing technology within its supply chain.